Indonesia's humanitarian (b)order and the multiple movements of Rohingya refugees - Koh, Sylvia (Nanyang Technological University, 2021)
Despite Indonesia’s increased policing of its borders to counter irregular migration since 2000 and the claims that the country is increasingly a ‘cul de sac’ rather than a point of transit, successive waves of Rohingya refugees have not only managed to arrive in Aceh by boat, but have also continually been able to leave their shelters and camps to seek relatives and employment opportunities in neighbouring Malaysia. Yet, this recurring phenomenon of Rohingya arrival and departure remains understudied in the context of Indonesia’s humanitarian border. This paper adopts a processual border approach to examine the ways in which the humanitarian border regime differentiates migrants and attempts to regulate their movements based on particular forms of humanitarian knowledge. It then maps how these dominant forms of humanitarian knowledge and categories are contested and problematised at different sites and scales, namely, in the regional province of Aceh and through the movements of Rohingya migrants which are shaped by their ethnic and gendered identities. In problematising established humanitarian categories, this paper raises imperative questions on humanitarian praxis and the manner in which protection and care ought to be delivered.